Restoration of Pancasila Values Against Criminal Law Reform Strategy in Indonesia Political Perspective of Islamic Law - Iqbal Kamalludin (Universitas Islam Negeri Antasari Banjarmasin, 2022)
Abstract: Criminal law is identical as miserable law, considering that criminal law is a means of last resort. Even though in its application, punishment must still prioritize the humanitarian element. Criminal law in Indonesia requires reform, because the substance of the Criminal Code is outdated and no longer in accordance with the objectives of criminal law as a means of protection and public welfare. This normative legal research uses a statutory and conceptual approach with prescriptive analysis techniques. The results of the research show that the Draft Criminal Code uses pro-Pancasila ideas and strategies as the philosophy of the Indonesian nation. Various forms of reform such as criminal alternatives, the development of the idea of balance, even the recognition of customary law which, although not written, upholds religious values, morality and humanity. Legal politics based on Pancasila, ideally contained in the formation of the concept of Indonesian criminal law, is an important substance and becomes a framework for the nation's morality from the threat of continued development of crime as a result of the evolving era.Keywords: Political Law, Criminal Law Reform, PancasilaAbstrak: Hukum pidana identik sebagai hukum yang menyengsarakan, hal ini mengingat hukum pidana merupakan sarana pengobat terakhir. Meskipun dalam penerapannya, pemidanaan harus tetap mengedepankan unsur kemanusiaan. Hukum pidana di Indonesia memerlukan pembaharuan, karena substansi KUHP telah usang dan tidak lagi sesuai dengan tujuan hukum pidana sebagai sarana perlindungan dan kesejahteraan masyarakat. Penelitian hukum normatif ini menggunakan pendekatan perundang-undangan dan konseptual dengan teknik analisis preskriptif. Hasil penelitian menunjukkan bahwa Rancangan Kitab Undang-Undang Hukum Pidana menggunakan ide-ide serta strategi pro-Pancasila sebagai falsafah bangsa Indonesia. Berbagai bentuk pembaharuan seperti alternatif pidana, pengembangan ide keseimbangan, bahkan pengakuan atas hukum Adat yang sekalipun tidak tertulis, menjunjung tinggi nilai religius, moralitas dan kemanusiaan. Politik hukum dengan berasaskan pada Pancasila, idealnya terkandung dalam pembentukan konsep hukum pidana Indonesia, merupakan substansi penting dan menjadi kerangka moralitas bangsa dari ancaman terus berkembangnya kriminalitas sebagai dampak dari zaman yang terus berkembang.Kata Kunci: Politik Hukum, Pembaharuan Hukum Pidana, Pancasila